CALCULATION OF STRESSED STATE OF ROCKS TAKING INTO ACCOUNT SEQUENCE OF THE FILLING MASS CONSTRUCTION - Seryakov V.M. (My University, 2001)
Methods of determining the stresses in rock mass have been considered. Influence of various factors on the stresses has been discussed. Method of evaluating the sequence of development of the mining and filling operation on the stressed state has been offered. Matrix of rigidity of scheme for calculating the stressed state remains constant at all stages of solving the problem. Examples of solving the problems show that constructed iteration algorithm is convergent. Opportunity for its efficient application has been demonstrated. Cases of exploitation of non-ferrous metal ore deposits have been considered.